Novel and Practical Industrial Process Scale-Up of 5-Bromo-2-chloro-4-(methoxycarbonyl)benzoic acid, a Key Intermediate in the Manufacturing of Therapeutic SGLT2 Inhibitors - Zhang, Yi; Ma, Xiao; Shan, Xiao-Hui; Zhang, Xiao-Wen; Li, Jian-Qi; Liu, Yu (Pharmaceutical Fronts, 2022)
5-Bromo-2-chloro-4-(methoxycarbonyl)benzoic acid (1) is a key intermediate for the synthesis of a family of promising SGLT2 inhibitors currently in preclinical and phase I studies for diabetes therapy. In this investigation, cheap, easily available dimethyl terephthalate was used as the raw starting material, and compound 1 was prepared effectively in six steps, including nitration, hydrolysis, hydrogenation, esterification, bromination, and diazotization. The preparation was run successfully on approximately 70 kg/batch with the total yield of 24%. This practical process was demonstrated to be scalable with a great yield and significant cost reduction.
Keywords: 5-bromo-2-chloro-4-(methoxycarbonyl)benzoic acid; SGLT2 inhibitors; practical process; scale up